Pengaruh ESG (Environmental, Social, and Governance) 1 terhadap Kinerja dan Nilai Perusahaan dengan Ukuran Perusahaan sebagai Variabel Moderasi - Cipto, Noventinus Surya; Hersugondo, Hersugondo (Universitas Katolik Soegijapranata, Semarang, 2024)
This study investigates the impact of ESG on company performance and value across various sectors of firms listed on the Indonesia Stock Exchange, with the size of the companies acting as a moderator. Company performance is evaluated through Return on Assets (ROA), while firm value is assessed using Tobin’s Q ratio (TQ). Control variables include Dividend Ratio (DIV) and Leverage (LEV), with firm size (SIZE) serving as a moderating factor. The research population comprises companies listed on the Indonesia Stock Exchange (IDX) from 2015 to 2022, with a sample size of 86 companies selected through purposive sampling. Panel data regression, incorporating Robust Standard Error, is employed for analysis, with the Fixed Effect Model (FEM) identified as the most suitable model. The findings reveal that the environmental (ENV) factor exhibits a non-significant negative influence on ROA but significantly impacts TQ in a negative manner. Meanwhile, social (SOC) factors demonstrate a significant positive effect on both ROA and TQ. Governance (GOV) displays a significant negative impact on ROA but positively affects TQ significantly. Furthermore, the interaction between environmental size (ENVSZ) and firm size yields a positive impact on both ROA and TQ, albeit significantly influencing only TQ. The interaction between social size (SOCSZ) and firm size, however, does not significantly affect either ROA or TQ. Finally, governance size (GOVSZ) exhibits a significant negative influence on both ROA and TQ.